The Role of the Additive Manufacturing Process Parameters in the Shaping of the Surface Geometric Structure During Micro-Milling - Marta KRAWCZYK; Bartosz POWALKA; Marcin MATUSZAK; Sebastian FRYSKA; Dariusz GRZESIAK; Pawel FIGIEL (Journal of Machine Engineering)
The article presents the results of measurements of the geometric structure of the surface after micro end-milling. In the experiments, coated monolithic super micrograin cemented carbide micro end mills with 2 flutes were employed. The machined parts were additively made of CoCr alloy using Selective Laser Melting technology (SLM). Analyzed variables were the volumetric density of energy supplied by the laser during the SLM process and the feed rate during micro-milling. The results showed a strong influence of SLM process parameters on the surface roughness, which, according to the authors, results from the significant variability of the mechanical properties of the material as a function of the volumetric density of energy supplied during melting.